Current clinical and epidemiological character of measles - I. V. Kuimova; E. I. Krasnova; E. N. Kibireva; N. I. Gavrilova; L. Yu. Chernyshova; O. A. Simkina (Лечащий Врач, 2021)
The article analyses the measles mobility in the time of the active immunization. The spread of infection in endemic areas revealed the cases only among non-vaccinated persons.